Перспективы электронного журнала «Проблемы телекоммуникаций» - Поповський, В. В. (Проблеми телекомунікацій, 2010)
In the opening remarks address there have been reflected the goal of creating of the electronic journal, its main goals and overall theme of the publications. Attention is paid to issues that are relevant to modern telecommunications and accentuated on the need of a systematic approach for solving scientific and practical problems in telecommunications.
Keywords: электронный журнал; телекоммуникации; системный подход; целостность; эмерджентность